Splitting the second: the story of atomic time - Jones, Tony (Institute of Physics Pub., 2011)
Until the 1950s timekeeping was based on the apparent motion of the Sun that in turn reflected the rotation of the Earth on its axis. But the Earth does not turn smoothly. By the 1940s it was clear that the length of the day fluctuated unpredictably and with it the length of the second. Astronomers wanted to redefine the second in terms of the motions of the Moon and the planets. Physicists wanted to dispense with astronomical time altogether and define the second in terms of the fundamental properties of atoms.